Perceived Factors of Influence on the Implementation of a Multidimensional Project to Improve Patients' Movement Behavior During Hospitalization: A Qualitative Study. Issue 2 (9th November 2021) - Bor, Petra; van Delft, Lotte; Valkenet, Karin; Veenhof, Cindy
Abstract: Objective: The aim of this study was to explore perceived factors of influence on the implementation of Hospital in Motion, a multidimensional and multidisciplinary implementation project to improve inpatients' movement behavior. Methods: This qualitative study was conducted on 4 wards. Per ward, a tailored action plan was implemented consisting of multiple tools and interventions to stimulate the integration of inpatient physical activity in usual care processes. After implementation, semi-structured interviews were performed with health care professionals and patients to explore perceived factors of influence on the implementation of the Hospital in Motion project. A content analysis was performed using the framework of the Medical Research Council for complex interventions as guidance for the identification of categories and themes. Results: In total, 16 interviews were conducted with health care professionals and 12 with patients. The results were categorized into the 3 key components of the Medical Research Council framework: implementation, mechanisms of impact, and context. An important factor of influence within the theme "implementation" was the iterative and multidisciplinary approach. Within the theme "mechanisms of impact, " continuous attention and the interaction of multiple interventions, tailored to the target group and targeting multiple dimensions (individual, inter-professional, community and society), were perceived as important. Within the theme "context, " the intrinsic motivation and inter-professional, community and societal culture towards physical activity was perceived to be of influence. Conclusion: Impact can be achieved and maintained by creating continuous attention to inpatient physical activity and by the interaction between different interventions and dimensions during implementation. To maintain enough focus, the amount of activities at one time should be limited. Impact: To improve inpatients' movement behavior, implementation project teams should be multidisciplinary and should implement a small set of tailored interventions that target multiple dimensions. Intermediate evaluation of the implementation process, strategies, and interventions is recommended.